Harnessing volatile luminescent lanthanide complexes to visualise latent fingermarks on nonporous surfaces. Issue 16 (17th July 2018) - Florence, Grace E.; Gee, William J.
Abstract : Sublimation of luminescent lanthanide complexes is shown here to be a facile means of visualising latent fingerprints on nonporous surfaces. Abstract : Two commercially-available terbium and europium complexes, EuFOD and TbTMHD, provide luminescent visualisation of latent fingermarks placed on nonporous surfaces via sublimation. This is demonstrated using UV radiation from a forensic light source. The method was optimised on metal foil, with other archetypal nonporous surfaces ( i.e. glass, ceramic) also suited to this method.